2016
DOI: 10.1187/cbe.16-01-0075
|View full text |Cite
|
Sign up to set email alerts
|

Options for Online Undergraduate Courses in Biology at American Colleges and Universities

Abstract: This analysis of online offerings in biology indicates that offerings at 2-year public colleges are common, while 4-year public and private institutions are lagging. Biology courses commonly offered online are general education and healthcare-related courses with limited options for biology majors. Ideas to increase biology online offerings are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…It appears that an analogous problem is arising with regard to online education. The number of courses offered online was notably increasing before the COVID-19 pandemic, with some STEM bachelor's degrees being offered completely online (Allen and Seaman, 2013;Varty, 2016;Cooper et al, 2019;Mead et al, 2020). Studies have shown that students with disabilities feel as though they have less overall support and fewer accommodations for their disabilities in online courses compared with their in-person courses (Terras et al, 2015(Terras et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that an analogous problem is arising with regard to online education. The number of courses offered online was notably increasing before the COVID-19 pandemic, with some STEM bachelor's degrees being offered completely online (Allen and Seaman, 2013;Varty, 2016;Cooper et al, 2019;Mead et al, 2020). Studies have shown that students with disabilities feel as though they have less overall support and fewer accommodations for their disabilities in online courses compared with their in-person courses (Terras et al, 2015(Terras et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Online learning makes higher education more accessible to a wider range of individuals as it creates educational opportunities that are free of time and geographic constraints (Varty, 2016). HESA data shows overall a higher number of females enroll on higher education courses; this trend is also seen in online providers e.g., The Open University, who reported a higher proportion of female to male students ratio in 2019/20 (The Open University, 2021).…”
Section: Social Media Usagementioning
confidence: 99%
“…Because fully online education removes many of the constraints imposed by a brick and mortar location, it has enormous potential to increase access to students who may otherwise not be able to pursue a college degree [ 3 ]. First, online education could increase access for higher education for students who live in education deserts.…”
Section: Introductionmentioning
confidence: 99%